Leveraging the Responsibility Factor in the Business Courses for Hungarian and International Computer Science Students and Evaluating the Implications on their Entrepreneurial Ideas: the Case of ELTE Faculty of Informatics - Barbara Hegyi; Boglárka Mucsi; Katalin Nádasi (Management, 2025)
Research Question: The main research question of the study is whether computer science changes students’ awareness in regard of how the role of social impact is demonstrable along the different courses due to embedded lectures and methodologies in basic entrepreneurship courses. Motivation: There are only limited research results available in relation to the awareness of students towards social responsibility (Rubic & Pavelic, 2023; Taboada et al., 2024; Hilt et al., 2024; Siqueira et al., 2023), mainly when it comes to students in tech, although their role in the development of the future responsible innovations will be crucial (Hwang, 2023; Howland, 2024). Idea: The idea of the study is to introduce those results that targeted the mapping of students’ attitudes towards social responsibility in general, the efficiency of deepening their knowledge in this regard and the social responsibility factor component of their individual business ideas. Data: The change in the awareness and the different patterns originating from diverse student groups will be analyzed through three data sources that enable the induction of the depth of the acquired knowledge, based on data from a questionnaire-based survey, ration of correct answers in quizzes and the qualitative analysis of the individual ideas. The three data sources also refer to the expected progress that can be observed during the various phases of the courses and aim to contribute to the circumscription of differences in the interpretation of social impact. Findings: The study outlines conclusions on how effectively the knowledge regarding social impact can be transmitted in onsite and online basic entrepreneurship courses, identifying limitations in detecting deviation among the different groups of students. Our task was to examine, on the basis of preliminary knowledge what students think about the interrelations of profitability, positive social impact and competitiveness. The study also provides insights on how optimistic students are regarding profitability when it comes to the embracement of social aspects and in what phase of the venture development they can imagine concentrating on social issues. An introduction is presented on how the level of understanding in relation to the nature of social impact strategies changed along the courses. The analysis of the acquired knowledge and how it reflects in the individual business ideas is based on a scale for categorization that incorporates the typical patterns of the involvement of the social impact factor. Contribution: Educators and course designers striving to embrace a special element as a main focus in their innovation and entrepreneurship education might use the introduced approach as a potential tool to analyze the change in the depth of knowledge in regard of social responsibility.